Uso da somatotropina recombinante bovina em búfalas leiteiras II: metabolismos energético e mineral - Melo, W.o.; Nascimento Júnior, A.s.; Monteiro, B. M.; Ribeiro Filho, J.d.; Faturi, C.; Daher, L.c.c.; Souza, D.c.; Sousa, E.m.; Faria Júnior, S.p.; Viana, R.b. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2019)
ABSTRACT The aim was to evaluate the influence of recombinant bovine somatotropin (rbST) on the energy and mineral metabolism of buffaloes between 63 - 154 days in milk. Twenty-two buffaloes distributed in two experimental groups were used: Group rbST (n= 11) - application of 500mg of rbST every 14 days; Control Group (n= 11) - no rbST. Every seven days, blood samples were taken to determine the biochemical profile, and milk production and body condition score were measured. The averages of the variables for rbST and Control groups were, respectively: milk yield (MY) - 6.44kg vs. 6.68kg; body condition score (BCS) - 3.51 vs 3.57 (1-5); glucose - 70.58 vs. 64.81mg/dL (P = 0.0003); cholesterol - 132.38 vs. 133.40mg/dL; triglycerides -29.18 vs. 28.32mg/dL; total protein - 8.57 vs. 8.75g/dL; albumin - 3.47 vs 3.60g/dL; urea - 32.46 vs 33.86mg/dL; creatinine - 1.27 vs 1.39mg/dL; calcium - 10.25 vs. 10.73mg/dL; phosphorus - 5.76 vs 5.62mg/dL; and magnesium - 3.70 vs 3.70mg/dL. Use of 500mg rbST influenced glucose metabolism, but did not modify the MY, BCS and the levels of the other metabolic parameters studied.

RESUMO Avaliou-se a influência da somatotropina recombinante bovina (rbST) sobre os metabolismos energético e mineral de búfalas entre 63e 154 dias em lactação. Foram utilizadas 22 búfalas, distribuídas em dois grupos experimentais: grupo rbST - aplicação de 500mg de rbST a cada 14 dias; grupo Controle - sem aplicação de rbST. A cada sete dias, foram coletadas amostras de sangue para a determinação do perfil bioquímico e mensuraram-se a produção de leite e o escore de condição corporal dos animais. As médias dos parâmetros estudados para os grupos rbST e Controle foram, respectivamente: produção de leite (PL): 6,44kg vs. 6,68kg; escore de condição corporal-ECC (1-5): 3,51 vs. 3,57; glicose: 70,58 vs. 64,81mg/dL (P = 0,0003); colesterol: 132,38 vs. 133,40mg/dL; triglicérides: 29,18 vs. 28,32mg/dL; proteína total: 8,57 vs. 8,75g/dL; albumina: 3,47 vs. 3,60g/dL; ureia: 32,46 vs. 33,86mg/dL; creatinina: 1,27 vs. 1,39mg/dL; cálcio:10,25 vs. 10,73mg/dL; fósforo:5,76 vs. 5,62mg/dL; e magnésio:3,70 vs. 3,70mg/dL. O uso de 500mg de rbSTinfluenciou o metabolismo da glicose, porém não modificou a PL, o ECC e os níveis dos demais parâmetros metabólicos estudados.
Use of recombinant bovine somatotropin (rbST) in dairy buffaloes II: energy and mineral metabolism
Keywords: growth hormone; milk production; blood metabolites; Bubalusbubalis; hormônio do crescimento; produção de leite; metabólito sanguíneo